2003
DOI: 10.1046/j.1365-2141.2003.04435.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a single, weekly dose of recombinant erythropoietin in myelodysplastic syndromes

Abstract: Summary. Thirteen patients with low-to-intermediate risk myelodysplastic syndrome (MDS) received recombinant erythropoietin (r-EPO) at the single, weekly dose of 40AE000 U for at least 8 weeks. Five patients (38AE4%) achieved a major erythroid response (increased haemoglobin levels > 2 g/dl and/or transfusion independence), which is currently maintained after 3-11 months, without modification of r-EPO dose. This study suggests that 40AE000 U r-EPO given once a week may be at least as effective as the more freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 9 publications
2
29
0
1
Order By: Relevance
“…This is a practical model for treatment, but it does not exclude other efficacious modalities. A recently published pilot study showed that once-weekly dosing of Epo is probably feasible, 23 but larger studies are needed to confirm this finding. In the present study, required maintenance doses of Epo and G-CSF did not differ significantly between the FAB groups.…”
Section: Discussionmentioning
confidence: 85%
“…This is a practical model for treatment, but it does not exclude other efficacious modalities. A recently published pilot study showed that once-weekly dosing of Epo is probably feasible, 23 but larger studies are needed to confirm this finding. In the present study, required maintenance doses of Epo and G-CSF did not differ significantly between the FAB groups.…”
Section: Discussionmentioning
confidence: 85%
“…20,21,[24][25][26][27][28][29][30] Studies with erythropoietin and darbepoetin alfa in low-risk MDS identified transfusion independence as significant for QOL and showed primarily erythroid responses (major HI-E in 29%-47% and minor HI-E in 26%-30% in various studies) without improvements in platelets or granulocytes. 24,[31][32][33][34][35][36] A recent study of thalidomide in lower-risk MDS defined its role more precisely. At thalidomide doses of 100 to 400 mg daily, responses after more than 3 months of therapy were observed in 14 of 82 patients.…”
Section: Evaluating Treatment Effects On Chronic Cytopeniasmentioning
confidence: 99%
“…Other inclusion criteria were as follows: documented significant cytopenia for more than 2 months and ineligibility for stem cell bone marrow transplantation (BMT). Patients were excluded for prior allogeneic BMT, cytogenetic abnormalities consistent with de novo AML (such as t (15,17), t(9,11), t (8,21), t(9,22), t (8,16), and inv16), 25,26 proliferative chronic myelomonocytic leukemia (CMML), prior leukemia, rapidly progressive AML, chronic myelogenous leukemia (CML) blast crisis, use of oral corticosteroids (Ͼ 10 mg), history of hepatitis B/C, HIV, or an active infection requiring intravenous antibiotics.…”
Section: Patientsmentioning
confidence: 99%
“…Recently, weekly dosing of recombinant human erythropoietin alpha therapy resulted in improvement in erythropoiesis in a subset of MDS patients who were unresponsive to conventional dosing. 17,18 Intensive chemotherapy induces complete remissions in 40% to 50% of patients but is associated with serious morbidity and mortality, with repeated and prolonged periods of hospitalization required and consequent impaired quality of life.…”
Section: Introductionmentioning
confidence: 99%